Persepsi Siswa tentang Pembelajaran Online pada Mata Pelajaran Ekonomi di Masa Pandemi Covid-19 - Fahimul Amri; Cahyo Tri Atmojo (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
This study aims to explain economic learning in secondary schools that was carried out online during the Covid-19 pandemic. This study used a quantitative approach. Collecting data through the survey method by giving questionnaires to respondents. Research respondents totaled 216 students. Data analysis was carried out descriptively by explaining the frequency, percentage, and mean score of the responses given by the respondents. The results showed that in online learning the teacher gave more assignments as well as delivered the subject matter, multi-way interaction between teachers and students has been built, students still have difficulty understanding the subject matter, students consider online learning carried out from home to be quite boring, students already have facilities ready. No need to come to school, flexibility, and save time and money are the advantages of online learning. Meanwhile, it is very dependent on the internet network, the availability of internet data packages, and redundant tasks are the weaknesses of online learning. Students tend to want learning to be carried out face-to-face and online (blended learning) during the Covid-19 pandemic